Modeling Gasoline Demand with Structural Breaks: New Evidence from Nigeria - Omisakin, Olusegun Akin; Oyinlola, Abimbola Mutiu; Adeniyi, Oluwatosin Ademola (International Journal of Energy Economics and Policy, 2011)
This paper extends previous studies in modeling and estimating demand for gasoline for Nigeria from 1977 to 2008. The ingenious attempt of this study, contrast to earlier studies on Nigeria and other developing countries, lies in its assumption of structural breaks in the long run relationship among the variables employed. The study tests for the possibility of structural breaks/regime shifts and parameter instability in the gasoline demand function in Nigeria using more recent and robust techniques. While the conventional residual-based cointegration tests employed fail to identify any meaningful long-run relationship in the gasoline function, the Gregory-Hansen structural break cointegration approach confirms the cointegration relationships despite the breakpoints. The elasticity estimates also follow the a priori expectations being inelastic both in the long- and short-run for both price and income. Having identified plausible breaks in the systems, the test does suggest that a structural break in the cointegration vector is important and needs to be taken care of in the specification of gasoline demand functions in Nigeria. It is envisaged, therefore, that substantial policy lessons would be drawn from the findings of this study especially in the current phase of energy industry deregulation in Nigeria. Keywords: Gasoline demand modeling; Structural breaks; Parameter stability; Cointegration JEL Classifications: C13; C22; C51